2014
DOI: 10.1007/s10832-014-9916-2
|View full text |Cite
|
Sign up to set email alerts
|

Size of oxide vacancies in fluorite and perovskite structured oxides

Abstract: An analysis of the effective radii of vacancies and the stoichiometric expansion coefficient is performed on metal oxides with fluorite and perovskite structures. Using the hard sphere model with Shannon ion radii we find that the effective radius of the oxide vacancy in fluorites increases with increasing ion radius of the host cation and that it is significantly smaller than the radius of the oxide ion in all cases, from 37 % smaller for HfO 2 to 13 % smaller for ThO 2 . The perovskite structured LaGaO 3 dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…16,21,24,25,27,[29][30][31][32][33] Stoichiometric expansion with substitution level is also employed to validate the substitution location. 25 35 Moreover, for other Fe-based perovskites (La 0.3 Sr 0.7 FeO 3-δ ), the stoichiometric expansion due to oxygen deficiency was experimentally found to be up to 5% at 900 o C. 36 As doping may also influence the oxygen deficiency in BFO, it is essential to develop a more detailed understanding of the geometric impact of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…16,21,24,25,27,[29][30][31][32][33] Stoichiometric expansion with substitution level is also employed to validate the substitution location. 25 35 Moreover, for other Fe-based perovskites (La 0.3 Sr 0.7 FeO 3-δ ), the stoichiometric expansion due to oxygen deficiency was experimentally found to be up to 5% at 900 o C. 36 As doping may also influence the oxygen deficiency in BFO, it is essential to develop a more detailed understanding of the geometric impact of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…O vacancies were formed because of the unbalanced charges between Fe 3+/2+ and Ti 4+ . Chatzichristodoulou et al reported that the effective radius of O vacancies (1.31Å) is smaller than that of the O anion ion (1.4Å), resulting in a decrease lattice constants 46 . The flaccidity of the size of O vacancies on the lattice parameters has a more significant influence than that of dopants in perovskite Bi 0.5 Na 0.5 TiO 3 or BaTiO 3 materials 30,47 .…”
mentioning
confidence: 99%
“…the relative change in ionic radius for Ce 4+ to Ce 3+ (18%) CeO 2Àd is larger than that for Co 4+ to Co 3+ (15%, high spin) and Fe 4+ 37 Though, as recently shown, a significant reason for the smaller a S of perovskites (ABO 3 ) as compared to ceria is related to the restraining action of the A-O sub-lattice to the expansion of the B-site cation upon reduction. 24 The fact that such structural constraints play a major role in the value of a S can also be inferred by the substantially different a S values found in the perovskite and K 2 NiF 4 structured oxides for vacancy formation (see Table 1), despite the fact that they contain the same reducible cations. In the case of the K 2 NiF 4 structured oxide, the 2-3 times smaller stoichiometric expansion coefficient along the a-direction versus the c-direction is attributed to the constraining action of the rock-salt layers on the perovskite layers.…”
Section: Preferred Definition and Choice Of Units For The Stoichiometmentioning
confidence: 94%
“…Sn, Si and LiCoO 2 . 18,19 Spurred by the above-mentioned issues, a significant research effort has been performed to uncover the origins of chemical expansion 6,[20][21][22][23][24] in order to guide research on developing new materials, compositions, and morphologies with reduced chemical expansion, as recently summarized by the authors. 1,25 In this article, caution is drawn to the generally accepted way the stoichiometric expansion coefficient is defined.…”
Section: Introductionmentioning
confidence: 99%